Analisis Strategi Segmentasi, Targeting dan Positioning (STP) Dalam Meningkatkan Pemasaran Produk Tabungan Smart IB Makbul Pada Nasabah Bank Sumut Syariah Simpang Kayu Besar - Tambunan, Ria Tifanny (ITB AAS INDONESIA Surakarta, 2024)
It cannot be denied that the economy must develop in accordance with the rapid development of the times. One of them is in the financial sector, where Islamic financial institutions are considered important and capable of overcoming the current economic crisis. The sharia banking industry in Indonesia continues to grow, one of the factors being the majority of Muslims. This situation convinced the Indonesian people of the importance of sharia in the economy and then established financial institutions to open banks with the aim of being able to provide the best to the community. In recent years, the banking industry has witnessed significant growth in demand for Islamic financial products. Of the many banking institutions that issue financial products including Hajj savings products, Bank Sumut Syariah is one of the sharia banking institutions that issues various financial products in accordance with sharia principles, one of the financial products developed by Bank Sumut Syariah is Savings Hajj. This research uses a qualitative research method with a descriptive approach. The results of this research, Bank Sumut Syariah Kcp Simpang Kayu Besar used geographic, demographic and behavioral segmentation. The target market applied uses Differentiated marketing with a relationship marketing approach. Furthermore, the positioning applied at Bank Sumut Syariah Kcp Syariah is by placing the product in a way that builds a positive image, builds customer trust and emphasizes the superiority of the Smart Ib Makbul Savings product.